Synthesizing Evidence and Testing the Militant Extremist Mindset Across Scales Version - Arifin, Haykal Hafizul; Lamuri, Aly; Kurniawan, Aryodi Wahyu; Milla, Mirra Noor; Mashuri, Ali; Takwin, Bagus (Psychological Research on Urban Society, 2026)
Extremist violence continues to pose serious risks in urban areas, yet tools for understanding these radical mindsets on the general population remain underdeveloped. Research on the Militant Extremist Mindset (MEM) is fragmented, with no synthesis of findings, unclear factor structure across shifting subscales, and little evidence from contexts with a documented history of extremist activity like Indonesia. This study addresses these gaps through two studies. First, we conducted a systematic review of empirical studies and a meta-analysis of 11 studies (N total = 5293) to examine the correlates of MEM’s three components - nastiness (endorsement of violence), grudge (hostile outlook), and excuse (moral or religious justifications for violence). Results on correlates of MEM were grouped into six themes: group/context, personality, identity, subclinical traits, social attitudes, and values. Study 2 analyzed three datasets of Indonesian participants (N total = 516) to reexamine the factor structure for each version of MEM scale. One version showed the best fit and relatively consistent intercorrelations. Theoretically, we propose viewing MEM as part of a motivational dynamic rather than a static list of traits within a certain taxonomy. These findings provide evidence for further cross cultural comparison of MEM scale and assess longitudinal changes in societal militancy, particularly in urban settings. We also provide an adapted version of the scale and outline final refinements for future research and practice.